BOVINE SERUM ALBUMIN FLUORESCENCE QUENCHING BY TANNIC ACID IN DIMETHYLSULFOXIDE CONTAINING SOLUTIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Bovine serum albumin (BSA) interaction with tannic acid (TA) has been studied in dimethylsulfoxide (DMSO) aqueous solutions at different temperatures (293 and 303 K). To find out the fluorescence quenching mechanism of BSA in the presence of TA, the fluorescence data were analyzed according to the modified Stern-Volmer equation based on the approach of the existence of a “sphere of action” (a type of apparent static quenching). The values of apparent static and bimolecular quenching constants were calculated. The effect of DMSO and temperature on BSA–TA interactions is explained on the basis of structural changes in the “sphere of action” of the fluorophore due to the possible inclusion of DMSO molecules in this sphere.
Keywords: bovine serum albumin; tannic acid; modified Stern-Volmer equation; dimethylsulfoxide; fluorescence; sphere of action